FAKTOR-FAKTOR PEMILIHAN PERBANKAN SYARIAH DAN KONVENSIONAL BERBASIS FLOATING MARKET DI PANGKAL PINANG BANGKA BELITUNG - Marheni Marheni (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2018)
This aims of study were to describe the characteristics of customers based on the floating market; find out the factors that influence the customer's decision in choosing a Shariah bank based on personal and social nature in Pangkal Pinang Bangka Belitung. This type of research was explanatary research. The population and sample were 100 respondents in the Pangkalpinang region. Methods of data analysis tools used logistic regression analysis tools. The test results showed that every gender difference did not affect the decision to choose a sharia bank and conventional bank. The age factor influences the decision to choose a sharia bank and conventional bank. Job status did not affect the decision to choose a Shariah bank and a conventional bank. Personal characteristics had a negative and significant effect on the decision to choose a sharia bank and conventional bank. Social system variables did not affect the decision to choose a sharia bank and a conventional bank.